Charge Transport in Two‐Photon Semiconducting Structures for Solar Fuels. Issue 20 (14th September 2016) - Liu, Guohua; Du, Kang; Haussener, Sophia; Wang, Kaiying
Abstract: Semiconducting heterostructures are emerging as promising light absorbers and offer effective electron–hole separation to drive solar chemistry. This technology relies on semiconductor composites or photoelectrodes that work in the presence of a redox mediator and that create cascade junctions to promote surface catalytic reactions. Rational tuning of their structures and compositions is crucial to fully exploit their functionality. In this review, we describe the possibilities of applying the two‐photon concept to the field of solar fuels. A wide range of strategies including the indirect combination of two semiconductors by a redox couple, direct coupling of two semiconductors, multicomponent structures with a conductive mediator, related photoelectrodes, as well as two‐photon cells are discussed for light energy harvesting and charge transport. Examples of charge extraction models from the literature are summarized to understand the mechanism of interfacial carrier dynamics and to rationalize experimental observations. We focus on a working principle of the constituent components and linking the photosynthetic activity with the proposed models. This work gives a new perspective on artificial photosynthesis by taking simultaneous advantages of photon absorption and charge transfer, outlining an encouraging roadmap towards solar fuels. Abstract : Burning bright : Progress on two‐photon semiconducting structures is presented with focus on understanding of interfacial carrier dynamics. Strategies from solution‐particle photocatalytic systems to nanostructured photoelectrode and photoelectrochemical devices are discussed to elucidate the mechanism of charge transport and to rationalize experimental observations. The studies compile valuable knowledge to build efficient solar‐driven systems for clean energy.